A longitudinal study of interpersonal relationships among lesbian, gay, and bisexual adolescents and young adults: Mediational pathways from attachment to romantic relationship quality - Starks, Tyrel J. (Arch Sex Behav, 2015)
The current study examined the potential for mental health to mediate associations between earlier attachment to parents and peers and later relationship adjustment during adolescence and young adulthood in a sample of sexual minority youth. Secondarily, the study examined associations between peer and parental attachment and relationship/dating milestones. Participants included 219 lesbian, gay, and bisexual youth who participated in six waves of data collection over 3.5 years. Parental attachment was associated with an older age of dating initiation, while peer attachment was associated with longer relationship length. Both peer and parental attachment were significantly associated with mental health in later adolescence and young adulthood. Mental health mediated the association between peer attachment and main partner relationship quality. While the total indirect effect of parental attachment on main partner relationship quality was statistically significant, specific indirect effects were not. Implications for the application of attachment theory and integration of interpersonal factors into mental health intervention with sexual minority youth are discussed.